2020
DOI: 10.3390/su12218919
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Trend and Its Relationship with Normalized Difference Vegetation Index in a Restored Semi-Arid Wetland of South Africa

Abstract: Clearance of terrestrial wetland vegetation and rainfall variations affect biodiversity. The rainfall trend–NDVI (Normalized Difference Vegetation Index) relationship was examined to assess the extent to which rainfall affects vegetation productivity within Nylsvley, Ramsar site in Limpopo Province, South Africa. Daily rainfall data measured from eight rainfall stations between 1950 and 2016 were used to generate seasonal and annual rainfall data. Mann-Kendall and quantile regression were applied to assess tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 80 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…The author reports that there was no significant trend in annual precipitation for most stations. Similarly, Murungweni et al 39 who studied data from 8 rainfall stations in the Limpopo province of South Africa between 1950 and 2016, report non-significant trends in annual and seasonal rainfall for station-specific available observation periods (except for one station). However, while the high interannual variability of annual precipitation data might mask trends, quantile regression analyses, indicate the presence of statistically significant up- and downwards trends.…”
Section: Discussionmentioning
confidence: 96%
“…The author reports that there was no significant trend in annual precipitation for most stations. Similarly, Murungweni et al 39 who studied data from 8 rainfall stations in the Limpopo province of South Africa between 1950 and 2016, report non-significant trends in annual and seasonal rainfall for station-specific available observation periods (except for one station). However, while the high interannual variability of annual precipitation data might mask trends, quantile regression analyses, indicate the presence of statistically significant up- and downwards trends.…”
Section: Discussionmentioning
confidence: 96%
“…The Tarim River Basin in the arid zone has shown an increasing trend in vegetation in recent years, and part of the vegetation degradation was related to downstream river breaks, overgrazing, and intensified human activities, which was similar to the causes of vegetation degradation in this study area ( Wang et al., 2023 ). According to a study of vegetation and rainfall in the semi-arid Nylsvley Wetland Reserve in South Africa, many years of drought and human activities have resulted in a negative pattern of NDVI ( Murungweni et al., 2020 ). On the contrary, the vegetation of the Lean wetland in the humid zone was in good condition and continues to be stable.…”
Section: Discussionmentioning
confidence: 99%
“…Banze et al (2018), from a review of rainfall trends in southern Africa, concluded that rainfall will both increase and decrease in the different parts of the region; however, there is still no total agreement among researchers on the magnitude of the anticipated rainfall change in the region. In contrast, Murungweni et al (2020), from a local-scale study in Limpopo (South Africa), established that there is a non-significant decrease in the annual rainfall.…”
Section: Rainfall Pattern and Trendsmentioning
confidence: 95%